2004
DOI: 10.1071/ea02055
|View full text |Cite
|
Sign up to set email alerts
|

Context evaluation: a profile of irrigator climate knowledge, needs and practices in the northern Murray - Darling Basin to aid development of climate-based decision support tools and information and dissemination of research

Abstract: Understanding client needs, knowledge and practices offers a means of ensuring research outputs match intended audience requirements. This paper shows the initial impact of context evaluation on the development of a suite of decision support tools and information to help irrigators better manage their water resources under different climatic conditions. The context evaluation study involved a survey of ~170 irrigators in the northern Murray�Darling Basin in Australia. It sought to clarify how they make croppin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…The irrigator study found that, as farm irrigation area increases, there was significantly ( P <0.001) higher use of the SOI in property decision making (Keogh et al 2004), compared with the grazier survey where there was no significant relationship.…”
Section: Comparing the Grazier Survey With The Irrigator Surveymentioning
confidence: 90%
See 1 more Smart Citation
“…The irrigator study found that, as farm irrigation area increases, there was significantly ( P <0.001) higher use of the SOI in property decision making (Keogh et al 2004), compared with the grazier survey where there was no significant relationship.…”
Section: Comparing the Grazier Survey With The Irrigator Surveymentioning
confidence: 90%
“…Our 43% sample response rate compares favourably with other mail-out surveys to farmers ranging from 6 to 65% that used a variety of methods for selecting their population. A mail survey of 2000 randomly selected farmers in the northern, central and southern tablelands of NSW achieved a 6% response rate (Bayley et al 1994); others surveyed a whole population, that is, all 931 regulated irrigators in the NSW and Queensland sections of the Northern Murray-Darling Basin received an 18.7% response rate (Keogh et al 2000a(Keogh et al , 2000b(Keogh et al , 2004; and all 2000 farmers in the northern wheat belt of NSW, 20% response rate (Hayman and Alston 1999). A purposive sample of selected Queensland graziers achieved a 65% response rate (Paull and Hall 1999).…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…The decisions made on pastoral properties using either weather or climate forecasts were similar in western Queensland. Third, in the northern Murray-Darling Basin a survey of irrigators in 1999 found 29% used the SOI in farm decisions including choice of crop and area, rate of fertiliser application, harvesting, sowing date, water availability and sales (Keogh et al 2004b). To accurately compare the results from the three studies above with our study, the wording of each question and its interpretation by the respondent should be identical in each case.…”
Section: How Did the Use Of Seasonal Forecasts Compare To Other Regions?mentioning
confidence: 92%
“…The low knowledge of some climate terms and concepts in the Australian agriculture sector is not a new finding (Coventry 2001;Dalgleish et al 2001;Keogh et al 2004aKeogh et al , 2004bKeogh et al , 2005, but it has not been demonstrated until now that the knowledge of climate terminology is similar between users and non-users of seasonal forecasts. Terms such as median and probability form the basis of many seasonal forecasts and a thorough understanding is important for their correct interpretation and use in decision making.…”
Section: Local Championsmentioning
confidence: 99%
“…Fifty-two percent correctly answered that northwest cloudbands are usually most prominent during April to August. Fifty-one percent correctly answered the question that the SOI is likely to be negative in an El Niño year compared to 68% of pastoralists surveyed in western Queensland in 2000 (n=41) and 91% of irrigators in the northern Murray-Darling Basin surveyed in 1999 (n=127) (Keogh et al 2004a(Keogh et al , 2004b. It was found that across the 3 surveys the difference between correct and incorrect responses to this question was highly significant (P<0.001).…”
Section: Do Pastoralists Understand the Technical Language Used In CLmentioning
confidence: 92%